2020
DOI: 10.3174/ajnr.a6764
|View full text |Cite
|
Sign up to set email alerts
|

Are Gadolinium-Enhanced MR Sequences Needed in Simultaneous 18F-FDG-PET/MRI for Tumor Delineation in Head and Neck Cancer?

Abstract: BACKGROUND AND PURPOSE: PET/MRI with 18 F-FDG has demonstrated the advantages of simultaneous PET and MR imaging in head and neck cancer imaging, MRI allowing excellent soft-tissue contrast, while PET provides metabolic information. The aim of this study was to evaluate the added value of gadolinium contrast-enhanced sequences in the tumor delineation of head and neck cancers on 18 F-FDG-PET/MR imaging. MATERIALS AND METHODS:Consecutive patients who underwent simultaneous head and neck 18 F-FDG-PET/MR imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…15 Pyatigorskaya et al reported a sensitivity of 90% and specificity of 98%. 22 Similar to the studies mentioned above, we achieved a high sensitivity of 91.7% and high specificity of 92.35%.…”
Section: Discussionsupporting
confidence: 83%
“…15 Pyatigorskaya et al reported a sensitivity of 90% and specificity of 98%. 22 Similar to the studies mentioned above, we achieved a high sensitivity of 91.7% and high specificity of 92.35%.…”
Section: Discussionsupporting
confidence: 83%
“…Recent literature has argued that gadolinium-enhanced MR images are not needed for accurate characterization of lesions because metabolic data from PET may offer similar information. 26 Thus, PET/MR imaging times could potentially be shortened even further.…”
Section: Discussionmentioning
confidence: 99%
“…In the first step, the tumor lesion was segmented on FDG PET images by thresholding 40% of the standardized maximum uptake value [ 19 ] to give the metabolic tumor volume ( Figure 1 (a1)). In the second step, the tumor lesion was segmented from the weighted MRI image set.…”
Section: Methodsmentioning
confidence: 99%